Bhutan : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bhutan. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
The pandemic has had a substantial impact on the economy, straining pre-pandemic gains in income and poverty reduction. The wide-ranging policy measures, including containment protocols, rapid vaccination and booster campaigns, direct income support, and policy support for borrowers and businesses, mitigated the adverse impact on lives and well-being. As the pandemic recedes and in light of the uncertainties from the war in Ukraine, the focus needs to be on securing livelihoods and ensuring strong and job-rich medium-term growth, while minimizing any persistent adverse effects from the pandemic and mitigating risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Bhutan